MENINGKATKAN KEMAMPUAN MENGENAL HURUF MENGGUNAKAN MEDIA KARTU HURUF PADA ANAK KELOMPOK B TK AL IHSAN KECAMATAN SUNGAI TABUK - Harlianty, Tien; Sjamsir, Hasbi (BEduManagers Journal : Borneo Educational Management and Research Journal, 2022)
This research is motivated by facts in the field which show that the ability to recognize letters in Group B of Al Ihsan Kindergarten is still lacking. Learning media available to introduce letters is still lacking, only using blackboards and LKA . The fun learning process to introduce letters is lacking and monotonous. In terms of language, especially the ability to recognize letters in group B children at TK Al Ihsan is still low. The low ability to recognize letters of kindergarten children will of course have a negative impact on those concerned. This impact will be greatly felt entering elementary school. So the researchers tried to apply the use of letter card media to improve the ability to recognize children's letters. The formulation of the problem in this study is how are children's learning activities in recognizing letters using letter card media? and how to improve children's learning outcomes in recognizing letters by using letter card media? The purpose of the research conducted was to find out an overview of the application of letter card media in improving the ability to recognize letters in group B children of Al Ihsan Kindergarten. The type of research used is classroom action research (CAR). The subjects in this study were the children of Al Ihsan Kindergarten Group B1 for the 2020/2021 academic year, which consisted of 10 children with 4 boys and 6 girls. Based on the research results obtained, it shows that the ability to recognize letters in group B1 children has increased. This is evidenced by the results of the achievement of child development which has increased in each cycle, namely (1) in cycle I, the achievement of child development is 70%. In cycle II, the achievement of child development was 90%. Thus, it can be concluded that the use of letter card media can improve the ability to recognize letters in group B1 children